Features of forest use in mountain protective forests of the Carpathian Region - Holubchak, Oleksiy; Hnatiuk, Oleg; Ivaniuk, Andriy (Forestry, Forest, Paper and Woodworking Industry, 2025)
It has been established that the area of mountain protective forests of the State Forestry Agency of Ukraine in the Ivano-Frankivsk region is 130,321.3 hectares, or 45% of the total area of such forests in Ukraine. In terms of species composition, spruce stands predominate in protective forests – 85.1%, beech accounts for 8.5%, fir – 2.8%, and the rest for other tree species (mountain pine, gray alder, weeping birch, maple, etc.) – 2.0%. The peculiarities of forest management in the mountain protective forests of the Ivano-Frankivsk region were studied based on an analysis of forestry measures carried out by area, type of work, and volume of timber harvesting for the period 2009-2020. During the study period, various forestry measures were carried out in the mountain protection forests of the State Forestry Agency of Ukraine in the Ivano-Frankivsk region, covering 55,947.1 hectares. In erosion control forests, the area covered by the measures ranged from 61.3 to 82.4%, and the volume of timber harvested ranged from 70.2 to 83.8%. In forests along river banks, around lakes, reservoirs, etc., the corresponding figures are 16.6-34.3% and 15.4-27.5%. It has been established that in forests of various subcategories of protective forests, regeneration and forest formation felling prevails, which was carried out on an area of 59.33%; other measures related to forest restoration and formation and measures related to forest management accounted for 14.31%; measures not related to forest management accounted for 9.51%; other forestry measures accounted for 16.57%. The majority of timber (90.74%) harvested during various forestry activities in protective forests is obtained through forest restoration and formation logging. In general, forestry activities in forests of various subcategories of protective forests of the State Forestry Agency of Ukraine in the Ivano-Frankivsk region are aimed at forming forest stands characterized by high biological stability and increased protective functions.